Carbon Dioxide Reduction: Visible and Near‐Infrared Photothermal Catalyzed Hydrogenation of Gaseous CO2 over Nanostructured Pd@Nb2O5 (Adv. Sci. 10/2016). Issue 10 (12th October 2016) - Jia, Jia; O'Brien, Paul G.; He, Le; Qiao, Qiao; Fei, Teng; Reyes, Laura M.; Burrow, Timothy E.; Dong, Yuchan; Liao, Kristine; Varela, Maria; Pennycook, Stephen J.; Hmadeh, Mohamad; et al.
Abstract : Some Like It Hot: Geoffry A. Ozin and co‐workers demonstrate that the reverse water gas shift (RWGS) reaction, driven by a visible and near infrared responsive Pd@Nb2 O5 is thermally activated with measured conversion rates as high as 1.8 mmol gcat −1 h −1, in article 1600189. Specifically, the RWGS reaction is enabled by heat generated from thermalization of photoexcited charge carriers in the Pd nanocrystals that function as "nanoheaters" for the entire Pd@Nb2 O5 assembly, through non‐radiative relaxation of inter‐band and intra‐band conduction electron transitions. Overall this study advances our understanding of the underlying mechanism of photothermally driven CO2 reduction. Cover illustration by Chenxi Qian.